Characterizing soils of Eastern Zambia - Omondi, John O; Mwila, Mulundu; Banda, Andson; Kyei-Boahen, Stephen; Chikoye, D. (2025)
Soil health and fertility play a critical role in determining crop productivity and sustainability in agricultural systems. In Zambia, declining soil fertility due to continuous cropping, minimal organic matter inputs, and nutrient imbalances threaten agricultural productivity. This study assessed the soil properties across four districts—Katete, Nyimba, Petauke, and Sinda—in Eastern Zambia to evaluate their fertility status and potential implications for crop production. The results indicated that the general soil pH across all districts was slightly acidic. However, some camps in Katete (18.3%), Nyimba (37.5%), and Sinda (26.3%) had neutral pH, whereas none in Petauke exhibited neutral conditions. Soil electrical conductivity (EC) was relatively high across the districts, with Nyimba having the highest levels. Sodium (Na) content was high in all districts, posing potential risks of soil degradation. Organic carbon (C), nitrogen (N), and cation exchange capacity (CEC) were generally low in Sinda, Katete, and Petauke, while Nyimba showed moderate levels. Notably, 12.5% and 26.3% of camps in Katete and Sinda, respectively, had very low organic carbon, while substantial proportions of camps in Katete (43.8%), Petauke (52.9%), and Sinda (42.1%) exhibited very low nitrogen levels. Phosphorus (P) levels were mostly moderate to high, except in Nyimba, where they were relatively low. Potassium (K) was generally moderate across districts, except in Nyimba, where it was high. Calcium (Ca) was low in Katete, Petauke, and Sinda, whereas magnesium (Mg) was high in those districts but significantly elevated in Nyimba. Soil texture varied, with most soils classified as sandy loam, except in Nyimba, where sandy clay loam and clay soils predominated. These findings underscore the need for targeted and site-specific soil fertility management practices, such as liming, organic matter additions, and balanced fertilization, to enhance soil health and crop yields in Eastern Zambia.